2x-9(x-4)=10

Enter Equation or Inequality


Solve for x in the equation 2x - 9(x - 4) = 10

We first need to simplify the expression removing parentheses
Simplify -9(x - 4): Distribute the -9 to each term in (x-4)
-9 * x = (-9 * 1)x = -9x
-9 * -4 = (-9 * -4) = 36
Our Total expanded term is -9x + 36

Our updated term to work with is 2x - 9x + 36 = 10

Step 1: Group the x terms on the left hand side:
(2 - 9)x = -7x

Step 2: Form modified equation
-7x + 36 = + 10

Step 3: Group constants:
We need to group our constants 36 and 10. To do that, we subtract 36 from both sides
-7x + 36 - 36 = 10 - 36

Step 4: Cancel 36 on the left side:
-7x = -26

Step 5: Divide each side of the equation by -7
-7x
-7
=
-26
-7

x = 3.7